Pengaruh Skeptisme Profesional, Risiko Audit, dan Ketaatan Prosedur Terhadap Tanggung Jawab Auditor Atas Kecurangan - Ahmad Ali Akbar; M. Adrian Muluk (Jurnal Ilmiah Manajemen, Ekonomi dan Akuntansi, 2025)
This study aims to examine whether there is an influence of Professional Skepticism, Audit Risk, and Compliance with Procedures on Auditor's Responsibility for Fraud. The population in this study were auditors who worked at KAP in South Jakarta. The number of samples in this study were 100 respondents. The sampling technique uses nonprobability sampling method. The research method used is quantitative with primary data sources. The methode of data analysis uses multiple linear regression analysis with SPSS version 25. The results of this study provide empirical evidence that partially professional skepticism has a positive and significant effect on auditor's responsibility for fraud, audit risk hasn’t effect on auditor's responsibility for fraud, and compliance with procedures has a positive and significant effect on auditor's responsibility for fraud.